Gênero textual propaganda radiofônica do tipo spot : um trabalho com sequência didática no projeto rádio recreio - Xavier, Cristiana de Jesus (2018)
This investigation is bound to the Research Group Alphabetization and School Literacy (ALFALE), of the Graduate Program in Education, of the Institute of Human and Social Sciences, of the Federal University of Mato Grosso - University Campus of Rondonópolis (PPGEdu/ICHS/UFMT/CUR), Brazil, in the research line “Languages, culture and construction of knowledge: historical and contemporary perspectives”. The theme of this study was the work with oral text genres, by means of Didactic Sequence (SD), through the project Radio in School, popularly known as Recess Radio, a dimension of Educommunication. The question which guided the research was: Which were the implications and the relevance of the work with oral text genres in the learning process of the students participants in the Recess Radio of the Santo Antônio State School, in the city of Rondonópolis-MT, through the use of didactic sequence as teaching strategy of the genre propaganda of the type spot? It is important to cite that such students attended the 6th and 9th years of Primary Education, in the school referenced above, which is an establishment of public education of Salesian orientation. As instruments of production and data gathering, the field diary, the written productions of the collaborating students, the planning of the DS, the photographic records and in audio of the oral productions of the participants, as well as the dialogues established with them were utilized seeking to highlight the experienced and the acknowledged in the group. Also, printed questionnaires and semi structured interviews (recorded in audio and transcribed) were conducted. This data was analyzed based on the works of authors like Bakhtin (1992), Bogdan and Biklen (1994), Dolz, Schneuwly, Noverraz and collaborators (2004), Severino (2007), Marcuschi (2008), Bronckart (1999), Thiollent (1987; 2011), Travaglia and coauthors (2013), among others. The main objective of the present research was to investigate which are the implications and the relevance of working with oral text genres in the learning process of the students participants of the Recess Radio of the Santo Antônio State School in Rondonópolis-MT, through the use of didactic sequence as teaching strategy of the genre radio propaganda of the type spot, being important to emphasize that the sequence adopted was the one constructed by the researchers of the University of Geneva (Switzerland), Dolz, Noverraz e Schneuwly (2004). It is also worth highlighting that the base of the discussion on text genre was guided by the assumptions of the sociodiscursive interactionism, therefore, the development of the study is characterized as a research of qualitative approach of action research. The data analysis revealed that the work with the oral text genre radio propaganda of the type spot, through the didactic sequence, was significant. The results indicate that there was a collective engagement in the activities developed by the researcher, along with the students. These presented growth in the learning of the structure of the genre under discussion, as well as the grammatical part and the prosodic (intonation, accentuation and rhythm).